Solar Assisted Dryer for Municipal Solid Waste - Pravin D.Pawale; Sumit S.Dharmarao; Prof. Dr. Maruti S.Pawar (International Journal of Innovations in Engineering Research and Technology, 2021)
Urban India generates 188,500 tons per day (68.8 million tons per year) of municipal solid waste (MSW) at a per capita waste generation rate of 500 grams/person/day. I mproper solid waste management deteriorates public health, degrades quality of life, and pollutes local air, water and land resources. It also causes global warming and climate change and impacts the entire planet. Im proper waste management is also identified as a cause of 22 human diseases and results in numerous premature deat hs every year. The composition of urban MSW in India is 51% organics, 17.5% recyclables (paper, pla stic, metal, and glass) and 31 % of inerts. The moisture content of urban MSW is 47% and the average calorific value is 7.3 MJ/kg (1745 kcal/kg). The composition of MSW in the North, East, South and Western regions of the country varied between 50-57% of organics, 16-19% of recyclables, 28-31% of inerts and 45-51% of moistur e. The calorific value of the waste varied between 6.8-9.8 MJ/kg (1,620-2,340 kcal/kg). Currently, there is no system or mechanism exists to dry the municipal solid waste. In this research work such syst em can be designed and developed which will dry the municipal solid waste and remove the odor from it. Dried municipal solid waste can be further used as fuel for boiler.